2022
DOI: 10.1088/1755-1315/977/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Increased soil pH due to the application of sulfate-reducing bacteria, rhizobia and amendments to acid sulfate soils planted with soybeans

Abstract: This study aims to determine the effect of the combination of Sulfate Reducing Bacteria, Rhizobia, and amendment matters on the soil pH acid sulfate soil planted with soybeans, carried out at the Greenhouse, Soil Biology Laboratory, Research Laboratory, Faculty of Agriculture, Universitas Sumatera Utara, from March to September 2021. This study used a factorial randomized block design with 2 factors and 3 replications. Each factor consists of 4 levels. The first factor were H0 (Control); H1 (Sulfate Reducing B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of this study indicate that the addition of microbial agents mainly composed of Bacillus, filamentous fungi, and lactic acid bacteria significantly increased the soil pH from 5.83 to 6.42. This may be related to microorganisms like Bacillus subtilis producing alkaline metabolites such as ammonia and carbonate, which can neutralize acidic substances in the soil and increase the pH value [33,34]. Luo et al [35] showed that film mulching can improve the physical and chemical properties of soil, such as by increasing soil moisture.…”
Section: Effect Of Microbial Agents and Mulch Film Covering On The Ph...mentioning
confidence: 99%
“…The results of this study indicate that the addition of microbial agents mainly composed of Bacillus, filamentous fungi, and lactic acid bacteria significantly increased the soil pH from 5.83 to 6.42. This may be related to microorganisms like Bacillus subtilis producing alkaline metabolites such as ammonia and carbonate, which can neutralize acidic substances in the soil and increase the pH value [33,34]. Luo et al [35] showed that film mulching can improve the physical and chemical properties of soil, such as by increasing soil moisture.…”
Section: Effect Of Microbial Agents and Mulch Film Covering On The Ph...mentioning
confidence: 99%